Boron‐doped Carbon Dots with Surface Oxygen Functional Groups as a Highly Sensitive and Label‐free Photoluminescence Probe for the Enhanced Detection of Mg2+ Ions. Issue 22 (9th June 2022) - Sadhanala, Hari Krishna; Pagidi, Sudhakar; Yadav, Suhas; Beiderman, Marianna; Grinberg, Ilya; Fixler, Dror; Gedanken, Aharon
Abstract: Magnesium ion (Mg 2+ ) is one of the most significant cations in living systems with involvement in many biochemical reactions and cellular processes and hence, sensitive and specific detection of Mg 2+ is therefore essential for various applications. Here, we report the solvothermal synthesis of boron‐doped carbon dots (BC10) with more oxygen surface states by using salicylaldehyde and naphthalene‐1‐boronic acid. The as‐prepared BC10 showed greenish‐white luminescence under 365 nm UV illumination with quantum yield (QY) of 5.5 % at optimum dilution with dimethyl sulfur oxide (DMSO) solvent. The BC10 in DMSO (DS‐BC10) have shown high selectivity and sensitivity towards Mg 2+ ion through the increased PL intensity due to chelation‐enhanced photoluminescence (CHEP). The enhanced PL intensity was further supported by the increased QY by a factor of 12 after the addition of Mg 2+ ions to 65.7 %. Moreover, the limit of detection of DS‐BC10 is calculated to be 0.4 μM, which is 100 times better than the recently reported carbon dot‐based Mg 2+ sensor. Following that, DS‐BC10 is also explored for detection of magnesium ions in lab tap water, seawater, and drinking mineral water with good precision. In addition, density functional theory (DFT) calculations using B3LYP/6‐31G (d) method for the DS‐BC10 and their Mg 2+ complexes support the experimental observations. Abstract : Oxidized functional groups containing BCDs, prepared at long duration (BC10), exhibited highly sensitive and selective Mg 2+ ion detection based on enhanced photoluminescence with LOD of 0.4 μM and in addition to this, QY of BCDs is also increased by a factor of 12 after the addition of Mg 2+ ions to 65.7 % in DMSO.